Drawing on the familiar to create new listening exercises (2001)
Many times language learners are vastly deficient in listening mastery while stronger in interpreting the written word or in speaking. This negative situation is oftentimes the result of insufficient opportunities available, for whatever reason, to language learners. Repetitive listening on “familiar ground” might be one way to help improve this drawback. This article attempts to deal with that familiar ground by giving examples and pointers vis-à-vis how to incorporate local characters, local historical figures, and local history and geography into listening exercises. Using this approach, students can more easily recognize in the second language facts and other data they already know in the first language